Introduction, for the 20th year of “Doctor Virtualis” (Doctor Virtualis, 2023)
The introduction to the issue Analogy and the Middle Ages sive twenty years of analogies presents issue n. 18 of "Doctor Virtualis" and traces the milestones of the journal. It first sketches some lines of the history of the journal and its main theoretical and historiographical inspirations, then highlights the reasons for the relevance of the theme of analogy, as an object used and thought of in the medieval centuries and as a tool for historiographical research, and finally concludes with the articulation of the issue.
Keywords: Doctor Virtualis; Analogy; History of Medieval Philosophy; Historiography